FUNCTIONAL COMPONENTS OF BEE PRODUCTS - Biber, Lejla; Ž. Kostić, Aleksandar; Kotorić, Hanka (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Bee products have been known to mankind since ancient times and their use is multiple. These products in their chemical composition contain numerous functional components that are of great importance for human health. Scientists are increasingly striving to invest in the functional components of these products and prove their benefits in nutrition and the treatment of many diseases. The aim of this paper is to describe how bees produce these products, describe their characteristics and the functional components found in them.